Implementasi Algoritma Winnowing Pada Aplikasi Kisah Para Nabi dan Rasul - Mirawati (Management of Information System Journal, 2022)
Books are a common learning medium used in telling the story of the prophet, but media such as books have several physical deficiencies that are easily damaged, and are less interactive which cause boredom easily, so we need a learning application about the stories of the Prophets and Messengers that can increase reading interest in the stories of the Prophets and Messengers in society. The purpose of this research is to determine the application procedure of the Prophets and Messengers. Implement an application that implements the winnowing algorithm in the application of the stories of the Prophets and Messengers. The benefits obtained by applying the winnowing algorithm in the application of the stories of the Prophets and Messengers are to increase interest in reading about the stories of the Prophets and Messengers.